Comparison of tests for trend in location and scale parameters in hydrological and precipitation time series - Agnieszka Rutkowska; Silvia Kohnová (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The objective was the comparison of properties of tests for trend in location and scale parameters for hydrological and precipitation time series, in particular (i) to review the non-parametric tests known from literature for various trends; the tests were studied from the point of view of their ability of detecting the existing trend (their power), (ii) to study the non-parametric tests for change in scale the power of which has not been estimated yet in application to hydrological and precipitation series (the Ansari-Bradley (AB), Siegel-Tukey (ST), Mood (M) tests), and (iii) to assess the differences between the tests.